Teorema de decomposição de Lévy-Itô - Pereira Junior, Silvano Antonio Alves (2014)
In this work we present an introduction to the study of Levy processes following those presented in the book (TANKOV, 2003). For this we will briefly review some results of the theory of Probability needed to the study. Then we study the Poisson processes, random measures and Poisson random measures. Next we introduce the Lévy processes and infinitely divisible distributions, we present the measure of Lévy and then the main result of this work, the Decomposition Theorem of Lévy-Itô .